A Critical Discourse Analysis on a Teenager’s with Progeria to Share an Empowering Life Philosophy: A Case Study on TEDX - Asnita Sirait; Budi Hermawan; Safrina Noorman; Chen Die (JOLLT Journal of Languages and Language Teaching, 2026)
This study aimed at investigating the strategy of a teenager with progeria to represent his identity and ideology through the analysis of transitivity and critical discourse analysis. This research applied a qualitative descriptive study. The data is taken from TEDx Talk https://www.youtube.com/watch?v=36m1o-tM05g entitled My philosophy for a happy life. The storyteller named Sam Bern told his life philosophy despite his disability due progeria disease. This study applied Fairclough’s approach (1989) on critical discourse analysis incorporating with Hallyday & Matthiessen’s SFL (2004) to the analysis of transitivity and discourse practice. The study found that the storyteller frequently used relational process with 39.79%, material process with 33.16%, and mental process with 24.62%. In relational process, the storyteller bravely defined himself, his condition, his sickness, and his struggle against progeria. Through material process, he represented himself as a dynamic and active person that even his disease or physical disability could not hinder him from doing what he could do. The study also found that Sam Bern showed his success in accepting himself as a child with progeria by trying to negotiate his identity and resilience. The implication of this study suggests that storytelling can be a powerful pedagogical resource for teachers and educators to promote resilience, identity formation, and positive values among students, particularly in contexts where personal challenges and diversity need to be addressed.